Six-years experience in major scalp defect reconstruction with free flap: analysis of the results - Innocenti, Alessandro; Menichini, Giulio; Innocenti, Marco (Acta Biomedica Atenei Parmensis, 2022)
IntroductionThe purposes of this study were to report 10-years experiences in microsurgical reconstruction of major scalp defects, comparing outcomes, evaluating complications. Materials and methodsFrom November to July 2015, 10 consecutive patients underwent microsurgical procedures for severe scalp defects.ResultsThe average age was 55,1 years ranging from 6 to 87 years. The mean follow-up was 16.7 months ranging from 12 to 24 months. The size of the lesions ranged from 9x10 to 16x20cm. The average hospital stay was 20 days ranging from 8 to 43 days. Mean operative times was 5.3 h ranging from 5 to 6.45 h. Free flaps included 8 Latissimus Dorsi flaps (LD) and 2 anterolateral thigh flaps (ALT). The superficial temporal vessels were used as recipient vessels in 9 cases while the superior Thyroid artery was used in remaining case.DiscussionFor large or complex lesions, the use of free flaps is mandatory. Nowadays LD and ALT flaps are among the most common reconstructive choices for scalp defects reconstructions. Older age does not contraindicate the operation procedure nevertheless in younger patients the size of vessels is proportionately larger and pristine. ConclusionMicrovascular free tissue transfer is the mainstay of scalp defects coverage. In our series early complications are less common and concerning than late complications and in fact reoperations are mainly required to manage these latter. Advanced age should be not consider a contraindication for free flap surgery and the procedure can be considered safe and reliable in both old and young population.